2019
DOI: 10.3906/sag-1807-79
|View full text |Cite
|
Sign up to set email alerts
|

Possible prediction of patterns of cervical lymph node spread based on primary tumor location in papillary thyroid carcinomas

Abstract: Backround/aim: Papillary thyroid carcinomas (PTC) frequently metastasize to regional lymph nodes. Our purpose was to investigate the predictive role of tumor location for lymph node metastasis pattern in PTCs. Materials and methods:Medical records of 110 PTC patients were reviewed retrospectively. Tumor location was determined as upper, middle, and lower pole according to ultrasonography (USG) findings. The effects of age, sex, tumor size, and location on lymph node metastasis were investigated. Results:The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…CLNM, which was the main contributor among all patients in our study, was observed at a lower rate in the upper pole group compared with the non-upper pole group. This result further indicates that there might be a direct lymph pathway from the upper pole of the thyroid to the lateral compartments, consistent with a previous report [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…CLNM, which was the main contributor among all patients in our study, was observed at a lower rate in the upper pole group compared with the non-upper pole group. This result further indicates that there might be a direct lymph pathway from the upper pole of the thyroid to the lateral compartments, consistent with a previous report [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, an increasing number of studies have reported that upper tumor location was related with LLNM in PTC and PTMC no matter whether central neck had metastatic lymph node or not (11,20,43,44). The presence of a direct lymphatic drainage from the upper third of thyroid to the neck may explain this finding (44,45).…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have reported that the risk of cervical LNM was associated with tumor location in PTC. [23][24][25][26] However, there is no research regarding the effect of tumor location on the risk of bilateral CLNM. One study showed that isthmus tumors were more likely to have CLNM than tumors in other locations.…”
Section: Discussionmentioning
confidence: 99%
“…26 Other studies demonstrated that the risk of lateral neck LNM was higher in upper pole tumors, and the risk of CLNM was much lower. [23][24][25] It is not clear why near-isthmus tumors are at a higher risk of bilateral CLNM. The possible mechanisms could be that PTC located in the near isthmus has similar characteristics as those located in the isthmus.…”
Section: Discussionmentioning
confidence: 99%